Productivity, response to nitrogen and nutrient cycling of sole jatropha (Jatropha curcas) and intercropping system with baby corn (Zea mays) in India - SHARMA, D K; RANA, D S (The Indian Journal of Agricultural Sciences, 2014)
Sole jatropha (Jatropha curcas L.) and intercropped system with baby corn (Zea mays L.) were evaluated for productivity, nutrient cycling, and economical viability under four levels of nitrogen at New Delhi, during 2007-09. Baby corn as intercrop under the 3-4 years old jatropha canopy received 65-70% of solar radiation during its growth period from February to April. Three rows of baby corn between the two rows of Jatropha interspaced at 3.0 m, recorded 819 and 765 kg baby corn yield/ha during 2007 and 2008. Sole and intercropped baby corn responded up to 80 kg N/ha. Sole jatropha recorded significantly higher seed yield (2.48 Mg/ha) than intercropped stand (2.23 Mg/ ha). Jatropha responded up to 40 kg N/ha in sole and 80 kg N/ha in intercropped stand. Based on two years mean, intercropped stand recorded an increase of 135% in productivity and 54% in land equivalent ratio as compared to sole Jatropha. Weed population and dry weight were found significantly low in intercropped stand. Jatropha produced 6 Mg/ha/year litter, which recycled 44.0 kg N, 7.4 kg P and 38.4 kg K/ha/year. At the termination of experiment, soil organic C in 0–15 cm soil depth in sole Jatropha (0.48%) and Jatropha + baby corn (0.49%) was found higher over the initial value (0.43). Conspicuous reduction in soil pH (7.4) and soil bulk density (1.46) were recorded compared to initial values (7.8 and 1.50). Water holding capacity of soil also recorded improvement over initial values.